How ESG Disclosure and Board Gender Diversity Shape Firm Value in Asia’s Industrial Sector Amidst Economic Uncertainty - Darma Irawanti Marbun; Sri Saraswati (Universitas Hayam Wuruk Perbanas, 2026)
This study investigates the effect of the environmental, social, and governance (ESG) disclosure score and board gender diversity on firm value in industrial sector companies across Asia during the 2021–2024 period. The analysis is based on a balanced panel of 209 firms observed over four years, resulting in 836 firm-year observations. Firm value is measured using Tobin’s Q, while the ESG disclosure score and board gender diversity are the main explanatory variables. Firm size and leverage are included as control variables. The study employs panel data regression analysis using the fixed-effects model (FEM), based on model selection tests. The results indicate that the ESG disclosure score has a negative and statistically significant effect on firm value, while board gender diversity also shows a negative but statistically insignificant influence. Control variables exhibit mixed effects, where firm size has a significant negative effect, and leverage is not statistically significant in explaining firm value across industrial firms in Asia. These findings confirm that sustainability disclosure and board composition have not yet been fully perceived as value-enhancing factors in short-term market valuation. The study contributes to the corporate governance and sustainability accounting literature by providing empirical evidence from Asian industrial firms and offers practical implications for corporate policymakers and investors in improving ESG implementation and board diversity strategies.